ESTAMOS TRATANDO DA LUTA DE CLASSES E DA REVOLUÇÃO? A APROPRIAÇÃO DO MARXISMO PELO GT TRABALHO E EDUCAÇÃO DA ANPEd SUL - BUCZEK, YOHANA GRAZIELY DE OLIVEIRA (2022)
Through this dissertation, we aim to understand the appropriation of the theory Marxiana in the articles published in the GT Work and Education of ANPEd Sul in the period between 2012 and 2020. Our main aim was to analyze how the categories Marxist ideas have been presented in the articles in relation to the foundations present in the marxian tradition. As a theoretical reference we use the guidelines of Materialism dialectical. With regard to the methodological procedures, we start from the proposed reading immanent by subsidizing a form of analysis that allowed us to understand the concreteness and the materiality of our object of investigation. In the analysis, we considered the socio-historical context of the production of the analyzed articles and the use of Marxian categories throughout of the text body. The research problem is outlined from the following questioning: how the theoretical categories of the marxian conception are presented discussed in the research published in the GT Work and Education of ANPEd Sul in the period between 2012–2020 in relation to class struggle and revolution? from this question guideline and the theoretical methodological framework adopted, we consider that our analyzes point out that Marxian references have been used as a discourse of authority in the text. Furthermore, they signal a process of emptying Marxian theory. This can be perceived as fundamental categories such as class struggle and revolution were not used properly in the analysis of the specific objects of each text.